Job loss and job instability during the COVID-19 pandemic and the risk of depression and anxiety among Swedish employees - Sandra Blomqvist; Robin S. Högnäs; Marianna Virtanen; Anthony D. LaMontagne; Linda L. Magnusson Hanson (Elsevier, 2023)
The COVID-19 pandemic led to permanent and temporary job losses but the mental health consequences of different types of employment transitions are not well-understood. In particular, knowledge is scarce concerning furloughs, which was a common job protection strategy in many high- and upper middle-income countries during this crisis. This study focuses on how different types of job instability and job loss during the pandemic influences depression and anxiety in the context of Sweden.A subset of participants from the Swedish Longitudinal Occupational Survey of Health were contacted in February 2021 and again in February 2022. A total of 1558 individuals participated in either or both waves and worked before the pandemic. We examined whether i) workplace downsizing, ii) furlough, or iii) unemployment/job loss were associated with depression and anxiety over this one-year period during the pandemic. Logistic regression models with cluster-robust standard errors were estimated, adjusting for sociodemographic factors and prior mental health problems. Effect modification by sex and prior mental health problems was also examined.In comparison to stable employment, being furloughed was unrelated to mental health, while experiencing workplace downsizing during the pandemic was associated with an increased risk of anxiety (adjusted Odds Ratio (OR) = 2.09, 95% Confidence interval (CI) = 1.08-4.05). Job loss/unemployment increased the risk of depression (OR = 1.91, 95% CI = 1.02-3.57) compared to being stably employed, but the risk estimate crossed unity when considering prior mental health status. No effect modification by sex or by prior mental health problems was found.This study found that while job loss and downsizing during the COVID-19 pandemic were associated with depression and anxiety, respectively, being furloughed was not. These findings thus suggest that job retention schemes in the form of short-time work allowances, as implemented in Sweden during the COVID-19 pandemic, may prevent mental health problems among employees during economic crises.